Methodical approach to an estimation of the financial and economic support of the chemical industry enterprises strategy - O. Chernysheva; N. Chupryna; O.P. Naumenko (Економічний вісник Державного вищого навчального закладу Український державний хіміко-технологічний університет, 2021)
The article is devoted to the substantiation of the content of the estimation components of the financial and economic support of the chemical industry enterprises strategy. The allocation of the estimation of the financial and economic support as a separate object on the process of strategic planning allows improving the level of validity of management decisions on the formation of the elements of enterprise strategy. It has been determined that sectors of the chemical industry are different by the level of technology, trends in sales dynamics, and profitability of activity. Analytical models of sales dynamics in the industry sectors have been built by the method of time series analysis. The inconsistency between sales volumes and financial and economic indicators in the strategy of industry’s enterprises has been revealed. This inconsistency does not allow ensuring the profitability of economic growth in the sectors. A methodical approach to an estimation of the financial and economic support of the chemical industry enterprises strategy has been offered. This approach involves estimation by components: the state of resource management and financial condition, resource efficiency and profitability of the enterprise. The estimation corresponds to the directions of the strategic development of the enterprise (market, marketing, production, and resource) and is the basis for decision-making of the elements of enterprise portfolio strategy (geographical vector of growth (market geography, demand, technology, and resources), competitive advantages, synergy and balance of strategic areas of management). Estimation of the financial and economic support of the domestic tire enterprises strategy according to the offered methodical approach proves that the formation of the elements of strategy should be carried out in the direction of improving the efficiency of resource use and providing the growth of enterprise profits on the basis of production and sale of competitive products.